Abū Ḥayyān al-Andalusī’s Thoughts on Qirā’āt Shādhdhah in The Tafsīr of al-Baḥr al-Muḥīṭ - Anisatul Fikriyah Aprilianti; M. Masrur Huda (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
In his tafsir work al-Baḥr al-Muḥīṭ, Abū Ḥayyān al-Andalusī is one of the scholars who has reviewed the interpretation of the Qur'an using linguistic analysis. The author of this research will go over Abu Hayya'n al-Andalusiy's opinions regarding qira, 'a, t sha, and dhdhah in the tafsir of al-Baḥr al-Muḥīṭ. Since it does not fit the requirements for the legitimacy of qirā’āt, qirā’āt shādhdhah is one of the ways of recitation that is still up for controversy among scholars. However, some commentators, such as Abū Ḥayyān al-Andalusī in the tafsir of al-Baḥr al-Muḥīṭ, utilize it to interpret the Qur'an. The ideas of Abū Ḥayyān al-Andalusī regarding qirā’āt shādhdhah are thoroughly examined in the linguistic domains of syntax, morphology, and phonology. The problem that has to be solved is this: How do Abū Ḥayyān al-Andalusī's ideas on qirā’āt shādhdhah fit into the understanding of al-Baḥr al-Muḥīṭ? This study employs a qualitative approach and is conducted in a library. It analyses Abū Ḥayyān al-Andalusī's views on qirā’āt shādhdhah in the context of al-Baḥr al-MuḥīṭThis study maps the ideas of Abū Ḥayyān al-Andalusī on qirā’āt shādhdhah in the linguistic features of phonology, morphology, and syntax in the interpretation of al-Baḥr al-Muḥīṭ. The results of the research of Abū Ḥayyān al-Andalusī on qirā’āt shādhdhah in the interpretation of al-Baḥr al-Muḥīṭ in the phonological, morphological, and syntactic domains are the study's outcomes. A portion of Abū Ḥayyān al-Andalusī's ideas regarding qirā’āt shādhdhah do not alter, but rather impact, reinforce, and broaden the meaning of interpretation.